PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SICEPAT EKSPRES BATAM - Elzan Fazira; M. Khoiri (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the effect of discipline and work motivation on employee performance at PT SiCepat Ekspres in Batam. Quantitative research is a type of research with a population of 110 people. Questionnaire is an instrument used for data collection. The sampling technique used a saturated sample, meaning that all of the population was sampled. data processing using SPSS version 26 with the results of the study it is known that discipline has a arithmetic value > t table that is 3.424 > 1.65922 with a significance of 0.001 < 0.05 which means that discipline has a positive and significant effect on employee performance, while work motivation tcount > t table namely 6.062 > 1.65922 with a significance of 0.000 <0.05, which means that monkey motivation has a positive and significant effect on employee performance. And motivation and discipline together have a positive and significant effect on employee performance. This is indicated by the results of the F test with a value of (F count) 54,984 > 2.69 (F table) with a significance value of 0.000 < 0.05. And the value of R square is 0.507.